2019
DOI: 10.1128/aac.00425-19
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Efficacy and Better Safety of Double β-Lactam Combination Therapy versus β‑Lactam plus Aminoglycoside in Gram-Negative Bacteria in Randomized, Controlled Trials

Abstract: There is a great need for efficacious therapies against Gram-negative bacteria. Double ␤-lactam combination(s) (DBL) are relatively safe, and preclinical data are promising; however, their clinical role has not been well defined. We conducted a metaanalysis of the clinical and microbiological efficacy of DBL compared to ␤-lactam plus aminoglycoside combinations (BLAG). PubMed, Embase, ISI Web of Knowledge, and Cochrane Controlled Trials Register database were searched through July 2018. We included randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 64 publications
0
39
0
2
Order By: Relevance
“…Dual ␤-lactam therapies are often avoided in clinical practice due to concern for potential toxicity. However, a recent meta-analysis of 13 randomized controlled trials assessed the efficacy and safety profiles of dual ␤-lactams compared to ␤-lactam plus aminoglycoside combinations against Gram-negative infections (80). This study found that dual ␤-lactams achieved slightly better clinical and microbiological responses, while conferring significant decreases in nephrotoxicity and ototoxicity compared to aminoglycoside-containing regimens, with the rates of other adverse events being largely comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Dual ␤-lactam therapies are often avoided in clinical practice due to concern for potential toxicity. However, a recent meta-analysis of 13 randomized controlled trials assessed the efficacy and safety profiles of dual ␤-lactams compared to ␤-lactam plus aminoglycoside combinations against Gram-negative infections (80). This study found that dual ␤-lactams achieved slightly better clinical and microbiological responses, while conferring significant decreases in nephrotoxicity and ototoxicity compared to aminoglycoside-containing regimens, with the rates of other adverse events being largely comparable.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to employ the LC-MS/MS assay in cassette and discrete modes and to demonstrate a lack of influx-related drug-drug interactions for the five ␤-lactams. Therefore, this assay enables characterization of the rate of OM permeability of double ␤-lactam combinations (12). The ranking of OM permeability coefficients matched between the discrete and cassette assay, and the results were comparable ( Table 1).…”
Section: Discussionmentioning
confidence: 73%
“…Double ␤-lactam combination therapy has shown promising efficacy in early clinical trials for patients with infections by susceptible Klebsiella spp. (12,34,35); this topic has received increasing attention. When each ␤-lactam inactivates its highest affinity PBP target, double ␤-lactam combination therapy offers the potential to inactivate an optimal set of PBPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel beta-lactam/beta-lactamase inhibitors (such as ceftazidime/avibactam) may be available treatment options, while poor use and rapid emergence of resistance restrict their application [16,17]. With less effective monotherapy and increasing resistance, evidence of retrospective studies on combination therapy of Gramnegative bacterial infections is increasing [18][19][20]. Many combination therapies have shown better survival and mortality reduction compared with monotherapy regimens, especially patients with a high predicted mortality [21][22][23].…”
Section: Introductionmentioning
confidence: 99%